Differential mast cell density in spectrum of benign neoplasms of breast: potential for patient stratification and personalised treatment approach - Dr. C.D. Anand; Dr. G. Shivashekar; Dr. S. Muthu; Dr. Amit kumar. Kalaivani; Dr. A. Sundaram (Tropical Journal of Pathology and Microbiology, 2019)
Background: Mast cells have a clear anti-tumorigenic role in invasive breast carcinoma. However, their role in the stepwise progression of benign fibroepithelial neoplasms of breast and mesenchymal tumours of the breast is less understood. Increased C-KIT (a receptor tyrosine kinase) expression in those tumours have been found to be due to presence of mast cells and a potential for patient stratification and individualized targeted therapy especially in phyllodes tumours. The present analysis was undertaken to assess the differential mast cell density within the spectrum of benign fibroepithelial neoplasms of the breast. Methods: Tissue from fifty three cases of fibroadenoma and it variants including cellular fibroadenoma, fibroadenoma with increased stromal cellularityand benign phyllodes tumour were included in the study. Mast cells were clearly demonstrated in breast tissue using Toluidine Blue stain at pH 2.3. Mast cells were counted using an eyepiece grid and expressed as no. of cells / per sq. mm, i.e., mast cell density (MCD). Differential mast cell density in spectrum of benign breast neoplasms was analysed and statistical analysis was done. Results: Mast cell density was statistically significantly higher in tissue from fibroadenoma compared to normal breast tissue. MCD was increased in cellular fibroadenoma and fibrodenoma with increased stromal cellularity compared to fibroadenoma. MCD was increased in benign phyllodes tumour compared to fibroadenoma with increased stromal cellularity, cellular fibroadenoma and fibroadenoma. Conclusions: Our results indicate a relative and progressive increase in mast cells in fibroadenomas compared to normal breast tissue and comparatively increased with increased cellularity and increased stromal cellularity among the spectrum of fibroepithelial neoplasms. The study could be extended with larger sample size especially of phyllodes tumours and combined with immunohistochemical (IHC) methods (antibodies for CD 117) could be used for patient stratification and selection for personalized treatment including anti-C-KIT therapy.